반 잠수형 쌍동선에 설치된 수중관람용 관람창 설계 및 구조 안전성 평가 - 황세윤(Se Yun Hwang); 김호성(Hosung Kim); 이경훈(Kyeong Hoon Lee); 김유일(Yooil Kim); 이장현(Jang Hyun Lee) (大韓造船學會 論文集, 2014)
In the design process of ship or its comprising components, the key to the successful design is how to guarantee the structural safety satisfying the international standard and regulation, which sometimes is not clear enough to cover the detail designs. This study deals with the design procedure for submersible viewing window installed in catamaran. As the window material, the Plexiglass, a type of reinforced plastic, is considered to satisfy the design requirements of international standard. Window thickness is calculated using geometric nonlinear finite element analysis, in order to take into account possible large deformation due to low stiffness of the Plexiglass, and the results are compared with those determined by the procedure specified in ISO12216. Finally, for the validation of proposed design, the pressure test had been carried out following the procedure specified in the standard, and structural safety was checked.